Thermodynamic study of the solubility of ethylparaben in acetonitrile + water cosolvent mixtures at different temperatures (2019)
The thermodynamic analysis of the solubility of ethylparaben (1) in acetonitrile (1) + water (2) cosolvent mixtures at 9 temperatures, 10 cosolvent mixtures and the 2 pure solvents, water and acetonitrile, is reported herein. The solution thermodynamic functions were calculated from the experimental solubility data, using the van't Hoff and Gibbs equations, following the approach proposed by Krug et al. Thus, the solubility of ethylparaben is thermo-dependent, reaching its minimum value in pure water at 278.15 K and its maximum value in the cosolvent mixture w1 = 0.90 at 318.18 K. The enthalpy of solution is positive in all cases, which is an indication of the endothermic process, with an enthalpy-driven mixing process in mixtures rich in water and by entropy mixtures rich in acetonitrile.